Effect of biosynthesized ZnO nanoparticles on the seed germination and seedling vigour index of sesame (Sesamum indicum L.): EFFECT OF BIOSYNTHESIZED ZnO NANOPARTICLES ON GERMINATION AND VIGOUR INDEX OF SESAME - P SARAVANANE; M DJANAGUIRAMAN; T RAMANADANE; K RAJA; S NADARADJAN (Journal of Oilseeds Research, 2021)
Sesame is an important oilseed crop, and the establishment of sesame in the field is critical because of its poor seed quality. One of the opportunities to improve seed germination and seedling establishment is the use of nanoparticles. Therefore, the studywas conducted toevaluate the effects of biosynthesized zinc oxide nanoparticles (ZnO NPs) from a medicinal weed, Tridex daisy (Tridex procumbens L.) on seed germination, and seedling vigour ofsesame (Sesamum indicum L.). Zinc oxide nanoparticles were synthesized through the green synthesis method by using zinc acetate as precursor and Tridax procumbens leaf extract as reductant. The synthesized product has been characterized byParticle Size Analyzer (PSA), UV-visible spectroscopy,scanning electron microscope (SEM), and transmission electron microscope (TEM). Then, the sesame seeds were treated with ZnO NPs, and seed germination and seedling vigour were quantified. The result indicated that the size of the ZnO NPs was 94 nm, assessed through a particle size analyzer. The UV-visible spectrum of synthesized colloidal ZnO NPs had the maximum absorbance peak at 298 nm. The SEM and TEM analysis indicates that ZnO NPs are spherical in shape. EDX confirms the purest form of Zn in ZnO NPs. The ZnO improved the seed germination and root growth of sesame compared to untreated control. Thus, it is evident that seed treatment with ZnO NPs can be a potential approach to improve the seedling establishment of sesame.